Synthesis and Catalytic Performance of Yb3+, Er3+ Doped Titanium Dioxide - He, Dongliang; Huang, Xiaowei; Zhao, Shanshan; Hu, Donghua (Asian Journal of Chemistry, 2015)
Titanium dioxide (TiO2) nano-materials have been widely applied into solving the environment and energy problems. However, common titanium dioxide materials can only absorb the ultraviolet light in the solar energy. In view of the unique 4f and empty 5d orbitals, rare earth element own special optical properties like Yb can convert the energy of infrared light into visible light which may be absorbed by Er in the catalytic process. Herein, we successfully doped the rare earth elements of Yb and Er into the TiO2 nano-material. The photo-catalytic activity of related titanium dioxide nano-material was enhanced through the excitation by visible and infrared light.